KEBIJAKAN PENAL PEMBEBASAN NARAPIDANA BERDASARKAN PERATURAN MENTERI HUKUM DAN HAM NOMOR 10 TAHUN 2020 TENTANG SYARAT PEMBERIAN ASIMILASI DAN HAK INTEGRASI BAGI NARAPIDANA DAN ANAK DALAM RANGKA PENCEGAHAN DAN PENANGGULANGAN PENYEBARAN COVID-19 DI INDONESIA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Corona Virus Disease 2019 or covid-19 is a contagious disease caused by the acute respiratory syndrome coronavirus. The spread of Covid-19 is taking place very quickly and one of the countries exposed to Covid-19 is Indonesia. One of the things that the government has done in preventing the spread of Covid-19 is releasing prisoners to prevent overcapacity. In writing this thesis, the author discusses the inmates who return to commit criminal acts after receiving assimilation. As for the purpose of writing this thesis, namely: First, to find out the penal policy for the release of prisoners based on the Minister of Law and Human Rights regulation number 10 of 2020. Second, to find out the policies of the Minister of Law and Human Rights Regulation No.10 of 2020 associated with the Correctional Objectives in Law Number 12 of 1995 concerning Corrections.This type of research is normative juridical research, namely research conducted by examining secondary legal materials or research based on standard rules that have been recorded and discussing synchronizing the law. Data sources used in this study are primary data, secondary data and tertiary data.From the results of this study it can be concluded that release of prisoners to prevent overcapacity in prisons and prevent transmission of covid-19, there are still some weaknesses so that it is not yet maximized in its implications. First, by emphasizing that there should be a re-harmonization or revision of the regulation of the Minister of Law and Human Rights number 10 of 2020 which still has some shortcomings or gaps in its application. So with that case can produce a good legal product. Second, that assimilated prisoners who return to commit criminal acts are not in accordance with the objectives of the correctional in Law number 12 of 1995. Requirements for prisoners to be released must be tightened so that no more prisoners return to commit criminal acts.Keywords : Convict - Assimilation – Correctional - Criminal Law Policy